(untitled) (Materiali di Estetica. Terza serie, 2019)
I interpreted "enthusiasm" as the only divine word that immediately produces life: from pneuma it becomes a vital, planning, creative practice. And describing the attempt to translate this reflection into didactic practice, I thought that another point of view would have been (certainly more pragmatic and less theoretical) abaut the meaning of the word of God in our social world. After all, the meaning of the word of God is read in the light that illuminates the look of man in the moment in which he intuits, discovers, understands, compares, creates. It matters little whether it is an idea born of a philosophical mind or a design of a dress on a new fabric: what matters is to have that idea or that tailored project and share its vital sense with others (not for an interest personal egoistic and infertile but for the community, in a fruitful and productive way), in a book or in the window of a shop, to offer another useful resource for the renewal of society. Below is an example model of interdisciplinary teaching with a philosophical matrix on the value of enthusiasm. This project was carried out within the civic engagement laboratory Legalità come prassi (Legality as praxis), born and developed within the Giovani Pensatori (Young Thinkers) university (Insubria University) project. Fifty students and twenty professors have worked with me to put into practice what has been designed together. It was an extraordinary work of research and didactic planning.